2020
DOI: 10.1186/s13024-020-00365-9
|View full text |Cite
|
Sign up to set email alerts
|

Dipeptide repeat proteins inhibit homology-directed DNA double strand break repair in C9ORF72 ALS/FTD

Abstract: Background: The C9ORF72 hexanucleotide repeat expansion is the most common known genetic cause of amyotrophic lateral sclerosis (ALS) and frontotemporal dementia (FTD), two fatal age-related neurodegenerative diseases. The C9ORF72 expansion encodes five dipeptide repeat proteins (DPRs) that are produced through a non-canonical translation mechanism. Among the DPRs, proline-arginine (PR), glycine-arginine (GR), and glycine-alanine (GA) are the most neurotoxic and increase the frequency of DNA double strand brea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
62
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 71 publications
(65 citation statements)
references
References 96 publications
3
62
0
Order By: Relevance
“…A non-canonical translation mechanism leads to the production of five dipeptide repeat proteins (DPRs) from the hexanucleotide repeat expanded C9ORF72 gene. A recent study indicated that, among the five DPRs, proline-arginine (PR), glycine-arginine (GR), and glycine-alanine (GA) are the most neurotoxic and decrease the efficiency of NHEJ, single-strand annealing and microhomology-mediated end joining (MMEJ) [ 118 ]. Consistently, increased levels of several DDR markers (γH2AX, phosphorylated ATM, cleaved PARP1 and 53BP1) were observed in spinal cord motor neurons of C9ORF72 ALS patients [ 119 ].…”
Section: Ndds Related To the Defective Dna Repair Mechanismsmentioning
confidence: 99%
“…A non-canonical translation mechanism leads to the production of five dipeptide repeat proteins (DPRs) from the hexanucleotide repeat expanded C9ORF72 gene. A recent study indicated that, among the five DPRs, proline-arginine (PR), glycine-arginine (GR), and glycine-alanine (GA) are the most neurotoxic and decrease the efficiency of NHEJ, single-strand annealing and microhomology-mediated end joining (MMEJ) [ 118 ]. Consistently, increased levels of several DDR markers (γH2AX, phosphorylated ATM, cleaved PARP1 and 53BP1) were observed in spinal cord motor neurons of C9ORF72 ALS patients [ 119 ].…”
Section: Ndds Related To the Defective Dna Repair Mechanismsmentioning
confidence: 99%
“…Besides protein sequestration and proteasomal inhibition, poly-GA expression was found to decrease the efficiency of DNA double-strand break repair mechanisms, specifically impacting non-homologous end joining, single-strand annealing, and microhomology-mediated end joining processes ( Andrade et al, 2020 ). Furthermore, mobile poly-GA aggregates can be found in the axons and dendrites of primary cortical and motor neurons overexpressing the poly-GA DPR ( Jensen et al, 2020 ).…”
Section: Non-arginine Dprsmentioning
confidence: 99%
“…Neurons are nonetheless capable of utilizing other repair pathways including single strand annealing (SSA) and microhomology-mediated end joining (MMEJ) that require small stretches of sequence homology (<25 nucleotides) to direct repair (Bhargava et al, 2016 ). Homology-directed DNA DSB repair pathways appear to be particularly relevant for the repair of transcribed DNA and may play a role in neurodegenerative disease (Keskin et al, 2014 ; McDevitt et al, 2018 ; Welty et al, 2018 ; Yasuhara et al, 2018 ; Andrade et al, 2020 ). Overall, accumulating DNA damage is characteristic of many neurological disorders, including aging and age-related neurodegenerative disease [for review consider (McKinnon, 2017 )].…”
Section: Causes and Consequences Of Dna Damagementioning
confidence: 99%